Evaluation of the Copper and Zinc Contents of Soils in the Vineyards of La Rioja (Spain) - Iñigo, Victoria; Marín, Álvaro; Andrades, Marisol; Jiménez-Ballesta, Raimundo (Environments - MDPI, 2020)
The aim of this study was to determine the concentrations of Cu and Zn in soils in the vineyards of La Rioja and to calculate reference values for the two elements. Samples were taken from the surface horizon (0–20 cm) and the subsurface horizon (40–60 cm) in 106 locations. Some physico-chemical properties were analyzed along with the total and bioavailable contents of these elements. Various statistical parameters were calculated, and distribution maps were then created using the ordinary-Kriging method. The Cu content was in the range of 2.46–121.52 mg kg–1, and the Zn content was 9.05–125.67 mg kg–1 . These values fell within the normal ranges in comparison with other areas of Spain and the rest of Europe. The concentrations in the surface and in the subsurface were compared; in the case of Cu, the concentration was higher at the surface, whereas significant differences in the vertical distribution of Zn were not observed. Both metals had a heterogeneous distribution across the entire area of study. In the case of Zn, the similarity of the maps between surface and depth was verified, while the case of Cu was different. The main source of these metals was the parent material from which the soil had been formed, but in the case of Cu, maps showed increased Cu at the surface, which was especially marked at certain points and seemed to indicate the presence of an exogenous contribution at these locations. That means that the copper concentrations in the topsoil resulted from the yearlong grapevine protection with copper-based agents. Reference values were calculated to be 85.28 and 48.88 mg kg–1 of Cu and 83.69 and 72.05 mg kg–1 for Zn at the surface and at depth, respectively.
Keywords: vineyard soils; reference levels; Cu content; Zn content; Cu distribution; Zn distribution; Scopus; Emerging